2022
DOI: 10.3390/cimb44080245
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Implications of Osteopontin in Heart Failure

Abstract: The matricellular protein osteopontin modulates cell–matrix interactions during tissue injury and healing. A complex multidomain structure of osteopontin enables it not only to bind diverse cell receptors but also to interact with various partners, including other extracellular matrix proteins, cytokines, and growth factors. Numerous studies have implicated osteopontin in the development and progression of myocardial remodeling in diverse cardiac diseases. Osteopontin influences myocardial remodeling by regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 186 publications
0
7
0
Order By: Relevance
“…Annexin A1, also known as lipocortin, has been mainly controlled by glucocorticoids hormons and cytosolic phospholipase A2 (PLA2) inhibition, responsible for the mechanism of arachidonic acid (ARA) release and the prevention of signaling molecules (eicosanoids) synthesis [ 137 , 138 , 139 ]. The protein itself has binding affinity to the phospholipid layers of the cell membranes, hence making it a molecular target for monitoring treatment response through cross-linkage with formyl peptide receptors [ 140 ]. With similar properties, cytoplasmatic annexin A2 has been largerly studied for its roles in intracellular regulation and cell signaling cascades [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Annexin A1, also known as lipocortin, has been mainly controlled by glucocorticoids hormons and cytosolic phospholipase A2 (PLA2) inhibition, responsible for the mechanism of arachidonic acid (ARA) release and the prevention of signaling molecules (eicosanoids) synthesis [ 137 , 138 , 139 ]. The protein itself has binding affinity to the phospholipid layers of the cell membranes, hence making it a molecular target for monitoring treatment response through cross-linkage with formyl peptide receptors [ 140 ]. With similar properties, cytoplasmatic annexin A2 has been largerly studied for its roles in intracellular regulation and cell signaling cascades [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…A few of the cell types in the heart that produce OPN in response to various stimuli, such as hypoxia, inflammation, toxin exposure, and mechanical stretching, include cardiomyocytes, cardiac fibroblasts, resident macrophages, and coronary artery endothelial cells. 74 OPN is an extracellular matrix protein that plays an integral role in myocardial remodeling and has previously been shown to be a valuable biomarker in CVD. 75 OPN, a plasma-detectable glycoprotein found to be elevated in various animal models of cardiac failure, may therefore constitute a new biomarker that makes it simpler for patients with HF to categorize their risks.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, we have demonstrated that NaHS treatment leads to a reduction in the OPN level in the plasma and muscles (gastrocnemius, tibialis anterior, and diaphragm) of mdx mice [162]. The role of OPN in the progression of cardiovascular diseases and heart failure is undeniable, and it was demonstrated in studies utilizing OPNnull mice and experiments with its depletion by neutralizing antibodies or via targeted mutagenesis (reviewed in [163,164]). It may also significantly influence DMD-related cardiomyopathy [165].…”
Section: H 2 S Is Anti-fibroticmentioning
confidence: 99%